2018
DOI: 10.1097/dss.0000000000001523
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study Investigating Changes in Body Image, Quality of Life, and Self-Esteem Following Minimally Invasive Cosmetic Procedures

Abstract: Minimally invasive cosmetic injectable procedures were associated with reductions in body image dissatisfaction. Future research, using recently developed cosmetic surgery-specific instruments, may provide further insight into the psychosocial benefits of minimally invasive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 42 publications
1
34
0
1
Order By: Relevance
“…The results of the present study extend work examine the relation between aesthetic procedures, self-esteem and body image dissatisfaction [15], while also added new findings about temperaments traits in patients with minimally invasive cosmetic procedures.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The results of the present study extend work examine the relation between aesthetic procedures, self-esteem and body image dissatisfaction [15], while also added new findings about temperaments traits in patients with minimally invasive cosmetic procedures.…”
Section: Discussionsupporting
confidence: 72%
“…Effects of cosmetic interventions on psychological outcomes are mixed; some findings indicated that satisfaction and self-esteem were positively associated with the minimally invasive cosmetic interventions, while in some studies no change in self-esteem was reported [14,15].…”
Section: Temperamentmentioning
confidence: 99%
“…Furthermore, patients have also noted associated improvements in psychosocial function. 29 Emerging studies have shown the benefit of combination therapy of filler with other technologies such as ablative fractional laser, 30 stem cells, 31 and platelet-rich plasma therapy. 32 Indeed, with the development of new dermal fillers on the horizon, in conjunction with other minimally invasive procedures such as neuromodulators, injectables, lasers, and devices, our ability to optimally recontour the aging face will continue to advance.…”
Section: Resultsmentioning
confidence: 99%
“…However, a few studies have investigated modifications in psychosocial functioning following these procedures (9). Some studies were performed to evaluate changes in cutaneous body image, self-esteem, and life quality following cosmetic injectable procedures with neuromodulators and soft tissue fillers (9). Cosmetic injectable treatments associated with an increase in body image satisfaction.…”
Section: Dear Editormentioning
confidence: 99%
“…Cosmetic injectable treatments associated with an increase in body image satisfaction. Further investigation using modern cosmetic surgeryspecific devices can supply new insights into the psychosocial advantages of cosmetic injectable treatments (9). Millions of cosmetic and surgical procedures of the face are administrated each year; however, objective clinical criteria that assess surgical procedures, such as complication rates, have limited efficiency when applied to cosmetic procedures.…”
Section: Dear Editormentioning
confidence: 99%